Boycott Or Buy? Exploring Consumer to Brand Betrayal and Brand Hate in The F&B Industry - Nabila Nurkhalisa; Muhammad Yasser Iqbal Daulay (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – Boycotts are a form of rejection that has been going on for a long time and has a significant impact on product sales, production and marketing . Aim – This study further explores the relationship between negative word of mouth, brand hate, brand betrayal and desire for avoidance in the context of the boycott phenomenon against fast food restaurants, McDonald's. Design / methodology / approach – This study focuses on consumers in Indonesia who have purchased McDonald's products both before and after the boycott. The method used in this study is quantitative with purposive sampling technique and the analysis tool is Smart-PLS-based Structural Equation Modeling (SEM). Findings – The results of this study show that there is an influence between the NWOM variable on brand hate and brand betrayal, brand hate influences desire for avoidance. However, NWOM and brand betrayal have no effect on desire for avoidance. Nevertheless, NWOM mediated by hatred of the brand is proven to directly influence the desire for avoidance, while when mediated by hatred of the brand, the effect is insignificant. Conclusion – This study reveals that a person's decision to continue buying or avoiding a boycotted brand is not solely influenced by negative information, but is also influenced by various factors, such as the need for the product. Research implications – Based on the results of this study, companies need to pay more attention to managing negative sentiment, especially on social media, to prevent the emergence of hatred towards brands that have the potential to cause long-term loss of consumers. Limitations – The limitation of this study is the limited number of consumers who boycott. Not all individuals will avoid boycotted brands due to religious beliefs, sympathy, or geographical limitations covering only one country.